2006
DOI: 10.1021/om0601192
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Evidence for the First Example of an Organolanthanide(II) Compound Having an Indenyl Ligand Bonded to the Metal through the Benzo Ring in η4 Hapticity

Abstract: The reaction of 2 equiv of C 9H6-1-SiMe3-3-CH2CH2NC5H10 (2) with the ytterbium(III) amide [(Me3Si)2N]3Yb-(μ-Cl)Li(THF)3 produced a novel ytterbium(II) complex with an indenyl ligand bonded to the metal via the benzo ring with η4 hapticity, [η4:η2:η1-(C5H10NCH2CH2C9H5SiMe3)Li(μ-Cl)]Yb-(η5:η1-C5H10NCH2CH2C9H5SiMe3) (1), as verified by a solid-state structure determination and theoretical calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The modularity of the Ind and Flu ligands is further increased by their ability to accommodate several easily interconvertible hapticities (so-called “ring slippage”). In particular, low Ind and Flu hapticities, which increase accessibility for the incoming substrates for both geometric and electronic reasons, have attracted considerable interest . Very significantly, Miller et al recently reported for the η 1 -complex B , featuring the sterically hindered (FluSiMe 2 N- t -Bu) 2− ligand (M = Zr, X = Cl, and L = Et 2 O), an inverted preference for α-olefin over ethylene polymerization (with homopolymerization activity typically 6 times higher toward propylene versus ethylene at 25 °C) and unprecedented stereoselectivity (resulting in syndiotactic polypropylene with melting temperatures as high as 165 °C). , This peculiar behavior further reinforces the interest for group 4 complexes featuring low coordinated Ind or Flu ligands, whose number and variety remain so far extremely limited.…”
Section: Introductionmentioning
confidence: 99%
“…The modularity of the Ind and Flu ligands is further increased by their ability to accommodate several easily interconvertible hapticities (so-called “ring slippage”). In particular, low Ind and Flu hapticities, which increase accessibility for the incoming substrates for both geometric and electronic reasons, have attracted considerable interest . Very significantly, Miller et al recently reported for the η 1 -complex B , featuring the sterically hindered (FluSiMe 2 N- t -Bu) 2− ligand (M = Zr, X = Cl, and L = Et 2 O), an inverted preference for α-olefin over ethylene polymerization (with homopolymerization activity typically 6 times higher toward propylene versus ethylene at 25 °C) and unprecedented stereoselectivity (resulting in syndiotactic polypropylene with melting temperatures as high as 165 °C). , This peculiar behavior further reinforces the interest for group 4 complexes featuring low coordinated Ind or Flu ligands, whose number and variety remain so far extremely limited.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of the indenes C 9 H 6 ‐1‐R‐3‐CH 2 SiMe 2 NC 4 H 8 (R = H, CH 3 ) with [(Me 3 Si) 2 N] 3 Eu III (μ‐Cl)Li(thf) 3 were also studied, and novel tetranuclear triple‐decker and monomeric europium(II) complexes were isolated and characterized 18a. A novel ytterbium(II) complex in which the indenyl ligand is bonded to the metal through the benzo ring with an η 4 ‐hapticity was isolated and characterized by treatment of the N ‐piperidinylethyl‐functionalized indene compound with the ytterbium(III) amide [(Me 3 Si) 2 N] 3 Yb(μ‐Cl)Li(THF) 3 18b. The above study indicated that the electronic and steric effects of the ligands have an influence on the homolytic reaction of the Ln–N (Ln = Yb, Eu) bond.…”
Section: Introductionmentioning
confidence: 99%
“…ansa-Bridged indenylamido complexes of titanium and niobium [17] and CH 2 -bridged pyrrolyl-indenyl complexes of lanthanides Sm, Yb and Eu [16] were reported. NR 2 -containing side chain-functionalized indenyl complexes of lanthanides Yb and Eu have demonstrated novel chemistry [18][19][20]. N-Heterocyclic carbene (NHC)-(CH 2 ) n -functionalized indenyl complexes of transition metals Ti, Zr, V, and Cr [21], and Ni [22], and lanthanide Y [21] have recently been documented.…”
Section: Introductionmentioning
confidence: 99%